ANALISIS TINGKAT KEPUASAN PENGGUNA TERHADAP APLIKASI TIERRA MENGGUNAKAN METODE PIECES FRAMEWORK - Filbert Alexander Tejokusuma; Husni Angriani; Afifah (STMIK KHARISMA Makassar, 2022)
TIERRA is a community application for ornamental plant lovers that can be used by users to interact with each other and can share experiences and help about ornamental plants. To improve and develop the TIERRA application, it is necessary to know the level of satisfaction of the TIERRA application by using the PIECES (Performance, Information, Economy, Control, Efficiency, Service) method as a method of measuring the level of user satisfaction. Based on the variables of the PIECES method, namely Performance, Information, Economy, Control, Efficiency and Service, the level of user satisfaction based on each variable is: Performance gets a value of 4.47, Information gets a value of 4.60, Economy gets a value of 4.24, Control gets a value of 4.31, Efficiency gets a value 4.46 and Service scored 4.37. Because each PIECES method variable is on a user satisfaction level scale of 3.4 – 4.91, then user satisfaction with the TIERRA application can be categorized as SATISFIED.